Compatibility issues of Industrialized Building System (IBS) in interior construction: a case study in Kuala Lumpur - Yaman, Rostam; Abdullah, Hamidon; Muhamad Halil, Faridah; Ahmad, Noraini (IOP Publishing Ltd, 2019)
The Construction Industry Development Board Malaysia (CIDB) defines Industrialized Building System (IBS) as a construction technique in which components are manufactured in a controlled environment (on or off-site), positioned, transported and assembled into a structure with minimal additional site works. Such as, a component that is being pre-fabricated in a controlled environment on-site are also considered as IBS. The main problem is when the contractors have bad workmanship while using pre-fabricated panels at the site and IBS components are deliberated to be inflexible with respect to be changes or renovations. The aim of this research to identify the issues of compatibility of Interior construction in IBS components. This study will concentrate on interior construction works using of IBS components. The importance of this research is to establish a design for a solution to the issues in using IBS components in interior constructions. This research also to develop design criteria of IBS components that have advantage and disadvantage in the interior construction industry in Malaysia. According to this study, the availability of knowledge and information on IBS components for interior construction will contribute to others. This research also develops new design criteria benefits to a designer using IBS components at the site. In the long term, this research will implement as a set of guidelines and additional knowledge that may encourage usage of user and CIDB.